High D(−) lactic acid levels production by Sporolactobacillus nakayamae and an efficient purification - Beitel, Susan Michelz [UNESP]; Sass, Daiane Cristina [UNESP]; Coelho, Luciana Fontes [UNESP]; Contiero, Jonas [UNESP] (Springer Nature, 2016)
This study is the first to report the efficient production of D(−) lactic acid by a strain of Sporolactobacillus nakayamae utilizing inexpensive peanut flour as a nitrogen source and commercial sucrose as a carbon source. A D(−) lactic acid concentration of 112.93 g/L was obtained by fermentation using 110.00 g/L of commercial sucrose, 150.40 g/L of peanut flour, and 0.16 ml/L of Tween 80. The optimal medium composition was determined using experimental design such as a Plackett-Burman, fractional factorial designs, and response surface methodology. The purification and recovery of D(−) lactic acid from the fermentation medium were performed using two purification techniques (filtration with activated carbon, followed by celite and cation resin exchange). This approach showed a high efficiency in protein and sugar removal as well in D(−) lactic acid recovery from the fermentation medium. Thus, the results indicate that S. nakayamae is a promising new D(−) lactic acid producer.
Keywords: D(−) Lactic acid; Isomers; Purification; Sporolactobacillus nakayamae; Submerged fermentation